2011
DOI: 10.1007/s00221-011-2982-7
|View full text |Cite
|
Sign up to set email alerts
|

The transition from implicit to explicit representations in incidental learning situations: more evidence from high-frequency EEG coupling

Abstract: Implicit learning, i.e. knowledge acquisition in incidental learning situations, is a fundamental feature of the human mind. The extraction of (and subsequent adaptation to) regular patterns in the environment facilitates everyday actions. The cognitive and neural processes accompanying the transition from subconscious (implicit) to verbally reportable (explicit) knowledge about task contingencies are of high interest to the cognitive neurosciences, since they indicate a process that generates awareness for le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 35 publications
5
36
0
Order By: Relevance
“…Singer (2011) adds, “brain states compatible with conscious processing should be characterized by a high degree of synchrony” (p. 43). Similar conclusions about the role of high frequencies in consciousness are found in the literature (e.g., Crick and Koch, 1990; Engel and Singer, 2001; Meador et al, 2002; Jung-Beeman et al, 2004; Doesburg et al, 2005; Aru and Bachmann, 2009; Doesburg et al, 2009; Uhlhaas et al, 2009; Hameroff, 2010; Wessel et al, 2012). Most recently, with the use of more sensitive technologies, the hypothesis was supported by Panagiotaropoulos et al (2012), who examined activities of the lateral prefrontal cortex of the macaque.…”
Section: Neurodynamicssupporting
confidence: 89%
“…Singer (2011) adds, “brain states compatible with conscious processing should be characterized by a high degree of synchrony” (p. 43). Similar conclusions about the role of high frequencies in consciousness are found in the literature (e.g., Crick and Koch, 1990; Engel and Singer, 2001; Meador et al, 2002; Jung-Beeman et al, 2004; Doesburg et al, 2005; Aru and Bachmann, 2009; Doesburg et al, 2009; Uhlhaas et al, 2009; Hameroff, 2010; Wessel et al, 2012). Most recently, with the use of more sensitive technologies, the hypothesis was supported by Panagiotaropoulos et al (2012), who examined activities of the lateral prefrontal cortex of the macaque.…”
Section: Neurodynamicssupporting
confidence: 89%
“…In that easier situation, about 50% of participants discovered the rule, and differences between rule-discoverers and non-discoverers did not exist from the very start but rather developed during task performance (cf. also Wessel, Haider, & Rose, 2012). Rose et al (2010) found that awareness for the regularity was preceded in rule-discoverers by an increase in neural activity Returning to our task, it is of interest that these group differences were visible in ERPs evoked in the first block even though response times for entering the responses with each pair did not differ between groups in the first block, F ≤ 1.3, ns, for effects of Group and Response Position × Group in ANOVA on the first block (thin lines in Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Instead of accumulating strength via feedback about the correctness of predictions, explicit attributional search processes result in sudden insights following the unexpected occurrence of predictive behavior. In an SRT task these sudden insights are characterized by an abrupt drop in the reaction times (Haider and Rose, 2007; Haider et al, 2011) as well as an increased coupling of gamma-band activity between the right prefrontal and occipital regions (Rose et al, 2010; Wessel et al, 2012). Hence, according to the UEH, consciousness about the sequence is not seen as a gradual matter, relying on a slow strengthening of associations on a trial-by trial basis, as proposed by single-system views or Cleeremans' hybrid model (Cleeremans, 2011).…”
Section: Introductionmentioning
confidence: 99%